METODE BERCERITA DALAM MEMBENTUK KARAKTER KEBERANIAN SISWA KELAS B DI RA AL MURTADHO KEDUNGWARU NGAWI - In'amu Dzakiyyatul Jamilah (Jurnal Penelitian Anak Usia Dini, 2022)
Courage is a character that can be formed by everyone.Good habits for character building in children are not enough to reach the family environment so that habits in the madrasa environment also need to be applied. One thing to note is in choosing the method given to children by using language that is easy to understand and the media used. This study uses a qualitative approach with the type of Classroom Action Research (CAR), which aims to find out how planning and the influence of the storytelling method in shaping the character of the courage of class B students at RA Al Murtadho Kedungwaru Ngawi. The number of subjects was 15 students who were students of class B RA Al Murtadho Kedungwaru Ngawi. Data obtained through observation, interviews, and evaluation. The result of this research shows that the has reached indicators in being brave and appearing confident when telling stories, showing a persistent and diligent attitude in learning, showing an honest and responsible attitude in answering teacher questions, and being able to show enthusiasm and enthusiasm in learning and playing. Abstrak Keberanian merupakan karakter yang dapat dibentuk oleh setiap orang. Pembiasaan baik untuk pembentukan karakter pada anak tidak cukup sampai pada lingkungan keluarga sehingga kebiasaan di lingkungan madrasah juga perlu diterapkan salah satu yang perlu diperhatikan adalah dalam memilih metode yang diberikan kepada anak dengan menggunakan bahasa yang mudah di pahami dan media yang digunakan.Penelitian ini menggunakan pendekatan kualitatif dengan jenis Penelitian Tindakan Kelas (PTK) yang bertujuan untuk mengetahui bagaimana perencanaan dan pengaruh metode bercerita dalam membentuk karakter keberanian siswa kelas B di RA Al Murtadho Kedungwaru Ngawi. Hasil penelitian menunjukkan adanya perkembangan yang telah mencapai indikator dalam berani dan tampil percaya diri ketika bercerita, menunjukkan sikap gigih dan tekun dalam belajar, menunjukkan sikap jujur dan bertanggungjawab dalam menjawab pertanyaan guru, serta dapat menunjukkan sikap antusias dan semangat dalam belajar dan bermain.